9.11 EFFECTIVENESS OF USING MODERN INNOVATIVE ACTIVITIES DURING THE LESSON - Muxamatjonova Diyora Rustam qizi, a foreign language teacher at Alfraganus University.; Ikromov Sherzod Akramovich, 1st grade of Tax and taxation at Alfraganus University (Innovative technologies in construction Scientific Journal, 2024)
This article deals with an effectiveness of modern methods in teaching foreign languages and interactive useful activities during the lesson. The main strategy of modern education should focus on the student's independent activity, the organization of self-learning environments and experimental and practical training, where students have a choice of actions and can use initiativedas well as flexible training programs where students can work in a comfortable rhythm. Today, we should talk about the use of interactive methods of training, which encourage interest in the profession; promote the efficient acquisition of training material; form patterns of conduct; provide high motivation, strength, knowledge, team spirit and freedom of expression; and most importantly, contribute to the complex competences of future specialistsTeaching styles have changed significantly over the years. Key words: Visualization, Cooperative learning, mathematical puzzles, Inquiry-based instruction INTRODUCTION. Traditional teaching The back-to-basics traditional education method, also known as conventional education, is still widely used in schools. The old-fashioned way of teaching was all about recitation, for example students would sit in silence, while one student after another would take it in turns to recite the lesson, until each one had been called upon. The teacher would listen to each student’s recitation, and they were expected to study and memorise the assignments. At the end of the module a written test or oral examination would be conducted; this process was called an Assignment Study Recitation Test. The way in which traditional methods were taught ensured that students were rewarded for their efforts, used class periods efficiently and exercised clear rules to manage students’ behaviour. They were based on established customs that had been used successfully in schools over many years. The teachers communicated the knowledge and enforced standards of behavior. Progressive modern teaching Education reforms mean that learning is taught from a completely different angle. Progressive educational practices focus more on the individual student's needs rather than assuming all students are at the same level of understanding. The modern way of teaching is more activity based, using questioning, explaining, demonstration and collaboration techniques.